Development of nanotechnology for processing chickpeas into protein plant supplements and their use to obtain a new generation of confectionery - Pavlyuk, Raisa; Pogarska, Viktoriya; Kotuyk, Tatyana; Pogarskiy, Aleksey; Balabai, Kateryna (Eastern-European Journal of Enterprise Technologies, 2020)
This paper reports the design of nanotechnology for processing chickpea into protein plant additives in the form of finely-dispersed pastes and nanopowders, based on the use of a deep processing method. A comprehensive effect exerted on the raw materials by the steam-thermal treatment and fine grinding using the modern equipment at restaurant enterprises has proven to be a real innovation. The technology involves the processes of steam- and mechanodestruction of most of the biopolymers in chickpea (proteins, starch, cellulose, pectin) to individual monomers (40...70 %), which are in the nanoscale easily-digestible form. The proposed method of deep processing makes it possible to better utilize the biological potential of raw materials. The resulting protein supplements made from chickpea in combination with fruit and vegetable additives (from carrot, pumpkin, apple, lemon with zest, garlic, celery and ginger roots) were used as formulation components in the development of a new generation of confectionery products that promote the strengthening of immunity. We have devised waffle confectionery products, sponge cakes, dry waffle breakfasts, salted fillings for the confectionery products "PanCake", etc. Confectionery of the new generation differs from the conventional one by the absence or insignificant amount of sugar, low content of fat (to 5 %), high content of complete protein (13...20 %). In addition, 100 g of products can meet the daily need for BAS (β-carotene, phenolic compounds) and 0.5 daily need for vitamin C. The resulting food products are natural and do not contain harmful food impurities